2021
DOI: 10.18502/ijm.v13i1.5489
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PCR and phenotypic methods for the detection of methicillin resistant Staphylococcus aureus

Abstract: Background and Objectives: Resistance to methicillin in methicillin resistant strains of Staphylococcus aureus (MRSA) is due to the presence of mec-A gene ,which encodes a low affinity penicillin binding protein (PBP)-2a or PBP2. Accurate and rapid identification of MRSA in clinical specimens is essential for timely decision on effective treatment. The aim of the study was to compare three different methods for detection of MRSA namely cefoxitin disc diffusion, CHROM agar MRSA and VITEK-2 susceptibility with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
2
13
1
2
Order By: Relevance
“…Accurate and rapid detection of MRS results support effective antimicrobial therapy, immediate patient isolation, and appropriate disinfection measures. Several methods for the detection of MRSA include latex agglutination assay, CHROM agar, VITEK, MALDI-TOF mass spectrometry, and PCR [14]. Although some of these methods are rapid, easy to perform, and are accurate in identification or detection, many of these methods are high in cost and have a high level of sophistication that requires operator experience and skill and special instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate and rapid detection of MRS results support effective antimicrobial therapy, immediate patient isolation, and appropriate disinfection measures. Several methods for the detection of MRSA include latex agglutination assay, CHROM agar, VITEK, MALDI-TOF mass spectrometry, and PCR [14]. Although some of these methods are rapid, easy to perform, and are accurate in identification or detection, many of these methods are high in cost and have a high level of sophistication that requires operator experience and skill and special instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…Using gold-standard methods, 72 MRSA and 28 MSSA were identified and the sensitivity and specificity of the chromogenic media for MRSA detection were 100% and 78.6%, respectively. Six false-positive MRSA were identified by the chromogenic media after 24 and 48 h of incubation; those six isolates were confirmed to be MSSA using other phenotypic methods [ 28 ]. In another study, the authors investigated 48 S. aureus subcultures to determine their methicillin resistance using chromogenic MRSA (RTA Laboratories, Kocaeli, Turkey).…”
Section: Phenotypic Methods For Antimicrobial Resistance Detection In S Aureusmentioning
confidence: 99%
“…Indeed, both those false negatives were detected as MRSA by VITEK 2 and chromogenic agar. The author suggested that in the case of a borderline inhibition zone diameter, a second confirmatory test might be necessary [ 28 ]. The disk diffusion method is a gold-standard method, and is accurate, reliable, easy to perform and low cost.…”
Section: Phenotypic Methods For Antimicrobial Resistance Detection In S Aureusmentioning
confidence: 99%
See 1 more Smart Citation
“…S. aureus isolates were obtained by standard microbiological techniques. Specimens were cultured on Columbia agar with 5% sheep blood (bioMe ´rieux, France), incubated for 24 hours aerobically at 37˚C, and identified by the tube coagulase test with rabbit plasma (Torlak, Belgrade) and confirmed by MALDI-TOF MS (VITEK MS, bioMe ´rieux) [5,6]. Methicillin resistance in S. aureus strains…”
Section: Specimen Types Culture Methods and Identificationmentioning
confidence: 99%